2023
DOI: 10.3390/diagnostics13040683
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Analysis of Deep Learning Methods in Breast Cancer Classification: A Structured Review

Abstract: Breast cancer is diagnosed using histopathological imaging. This task is extremely time-consuming due to high image complexity and volume. However, it is important to facilitate the early detection of breast cancer for medical intervention. Deep learning (DL) has become popular in medical imaging solutions and has demonstrated various levels of performance in diagnosing cancerous images. Nonetheless, achieving high precision while minimizing overfitting remains a significant challenge for classification soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…42 , 43 Recently, researchers have investigated the role of artificial intelligence and deep learning in detecting BC. 44 , 45 Innovation is becoming compulsory in the BCT field. 46 For all promising research findings, researchers propose their recommendations to professionals who work in the field, where these findings could lead to changes in the form improvements for their patients’ cases.…”
Section: Methodsmentioning
confidence: 99%
“…42 , 43 Recently, researchers have investigated the role of artificial intelligence and deep learning in detecting BC. 44 , 45 Innovation is becoming compulsory in the BCT field. 46 For all promising research findings, researchers propose their recommendations to professionals who work in the field, where these findings could lead to changes in the form improvements for their patients’ cases.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure more reliable outputs from machine learning models, it's vital to: (i) Increase the number of participants; (ii) Establish training, validation and test groups to limit overfitting. 241 from a variety of bodily fluids. Thorough analysis allows us to extract and interpret the information carried by these biomarkers.…”
Section: Machine Learning Assisted Optimization For Biomarker Isolationmentioning
confidence: 99%
“…However, machine learning models require large, multidimensional datasets that encompass various patient information including gender, age, type and stage of cancer, proteome, metabolome, level of biomarkers, and information contained within biomarkers, to avoid overfitting‐induced impressive accuracy but potentially misleading results. To ensure more reliable outputs from machine learning models, it's vital to: (i) Increase the number of participants; (ii) Establish training, validation and test groups to limit overfitting 241 …”
Section: Machine Learning Assisted Optimization Of Liquid Biopsymentioning
confidence: 99%
“…The use of medical data to enhance the accuracy of breast cancer diagnosis is widely recognized, as breast cancer remains the most prevalent cancer among women globally. For example, M. Yusoff et al [ 12 ] systematically analyzed 25 papers published from 2018 to 2020 and evaluated their methods and performance metrics. The results showed that CNNs were the most used deep learning approach for breast cancer classification, followed by ensemble methods and recurrent neural networks (RNNs).…”
mentioning
confidence: 99%
“…The study also highlighted limitations and challenges in the reviewed papers, such as limited sample sizes, lack of standardized datasets, and difficulty interpreting deep learning models’ decision-making process. In conclusion, the article provides a comprehensive overview of the current state of deep learning methods in breast cancer classification and identifies potential areas for future research [ 12 ].…”
mentioning
confidence: 99%